2023
DOI: 10.1039/d3nr04147f
|View full text |Cite
|
Sign up to set email alerts
|

Camptothecin-based prodrug nanomedicines for cancer therapy

Renshuai Zhang,
Jing Yu,
Zhu Guo
et al.

Abstract: Camptothecin (CPT) is a cytotoxic alkaloid that attenuates the replication cancer cells via blocking DNA topoisomerase 1. Despite its encouraging and wide spectrum antitumour activity, its application is significantly restricted...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 252 publications
(259 reference statements)
0
4
0
Order By: Relevance
“…Moreover, multifunctionality is a current focus, with research dedicated to constructing nanoscale delivery systems that integrate capabilities like controlled release, stimulus-responsive release, fluorescence imaging, and phototherapy, thereby offering a more holistic therapeutic approach. 108 4.2.1. Enhanced Permeability and Retention Effect.…”
Section: Structure−activity Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, multifunctionality is a current focus, with research dedicated to constructing nanoscale delivery systems that integrate capabilities like controlled release, stimulus-responsive release, fluorescence imaging, and phototherapy, thereby offering a more holistic therapeutic approach. 108 4.2.1. Enhanced Permeability and Retention Effect.…”
Section: Structure−activity Relationshipsmentioning
confidence: 99%
“…These systems can also achieve controlled drug release that maintains optimal drug concentrations over an extended period, thereby prolonging the circulation time of drugs, and stimuli-responsive release triggered by the tumor microenvironment further reduces off-target effects. Moreover, multifunctionality is a current focus, with research dedicated to constructing nanoscale delivery systems that integrate capabilities like controlled release, stimulus-responsive release, fluorescence imaging, and phototherapy, thereby offering a more holistic therapeutic approach …”
Section: Navigating the Complex Landscape Of Camptothecin Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Many clinical studies have shown that CPT and its derivatives can effectively inhibit a wide spectrum of human cancers, such as ovarian, bladder, colon, gastric, liver, leukemia, and breast cancers. 1–8 The structure–activity relationship indicated that the lactone ring in the structure of CPT significantly contributes to its anticancer activity. However, this could be broken into an inactive open loop through hydrolysis under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%